A reference in stage design for evangelical churches in Metro Manila - Alcaraz, Halee Starr B.
This study sought to provide a reference in the stage design of an evangelical church. Since there are no set guidelines available, this study may present the use and importance of design to enrich one's visual experience in a place of worship. Common visual components and meanings associated with it were also explored in this study. Utilizing cluster random method, sixty respondents from the three evangelical churches around Metro Manila were studied. These three respondent churches from Quezon City, Ortigas, and Manila were evaluated based on the size of its congregation and the presence of their own auditorium where they hold their church services. Respondents from these churches answered survey questionnaires regarding the visual components of stage design that are present in their respective churches. Five church leaders also underwent in-depth interview for the researcher to further understand the Christian faith. Findings showed that a church's image is manifested in the stage design and in the visual components present on it. It was also revealed in the study that some visual components express the church's core beliefs. Although the three churches have differences in their practice of the faith, the visual components found were similar such as band area, choir area, banners containing bible verses, and church's mission and vision statements, pulpit, and LCD screens. A list of reference in designing the stage of evangelical churches was developed. In this study, it was found that location, target audience, church's mission and vision statement, essential visual components found on stage, and layout and design execution are significant factors that should be used to enhance the design of the stage of these evangelical churches.